(untitled) (World Economics and Finance Bulletin, 2021)
This article deals with the problem of weak accounting rules about oil service contracts for the Iraqi Midland Oil Company and inconsistency with the requirements of (IFRSs). The research aims to show the results of the comparative application according to (IFRSs) because of the importance of what those contracts constitute from an economic point of view and providing appropriate and honest information to the oil decision-maker. Additionally, its goal is to evaluate a unified accounting system for oil service contracts and their implications for Indicators of the company’s financial performance (the research sample). To contribute to the development of the accounting dimension of the oil sector in light of its openness to joint work with international oil companies. The research point to several conclusions: The important one is the overall financial performance indicators of the research sample company indicate that the application of (IFRSs) was an indicator better than unified accounting system Indicators in a state of the company’s accounting application. The research recommends the necessity to pay attention to the study and analysis of the performance of oil companies and their financial conditions on an ongoing basis. Furthermore, to support the requirements of continuous evaluation of their performance due to the discrepancy and conflicting performance indicators due to the overlap of financial and accounting work.